2007
DOI: 10.1113/jphysiol.2006.121111
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐activated receptor 2 sensitizes the transient receptor potential vanilloid 4 ion channel to cause mechanical hyperalgesia in mice

Abstract: Exacerbated sensitivity to mechanical stimuli that are normally innocuous or mildly painful (mechanical allodynia and hyperalgesia) occurs during inflammation and underlies painful diseases. Proteases that are generated during inflammation and disease cleave protease-activated receptor 2 (PAR 2 ) on afferent nerves to cause mechanical hyperalgesia in the skin and intestine by unknown mechanisms. We hypothesized that PAR 2 -mediated mechanical hyperalgesia requires sensitization of the ion channel transient rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
347
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 352 publications
(374 citation statements)
references
References 59 publications
20
347
1
3
Order By: Relevance
“…Receptive fields were identified as described previously 5 , then tested with three distinct mechanical stimuli to enable classification: focal compression with calibrated von Frey hairs (70,160,400,1000mg, 2g & 4g force; each force applied for 3×3sec), mucosal stroking with calibrated von Frey hairs (10,200,500, and 1000mg; each applied 10 times) and circular stretch (1-5g, in 1g increments; each applied for 1 min, with 1 min interval between applications). Stretch was applied via a claw attached to the tissue near the receptive field connected to a cantilever system.…”
Section: In Vitro Electrophysiology and Pharmacologymentioning
confidence: 99%
“…Receptive fields were identified as described previously 5 , then tested with three distinct mechanical stimuli to enable classification: focal compression with calibrated von Frey hairs (70,160,400,1000mg, 2g & 4g force; each force applied for 3×3sec), mucosal stroking with calibrated von Frey hairs (10,200,500, and 1000mg; each applied 10 times) and circular stretch (1-5g, in 1g increments; each applied for 1 min, with 1 min interval between applications). Stretch was applied via a claw attached to the tissue near the receptive field connected to a cantilever system.…”
Section: In Vitro Electrophysiology and Pharmacologymentioning
confidence: 99%
“…Moreover, inhibition of PKC and PKA prevented the PAR-2 sensitization of TRPV1 calcium transients and currents as well as PAR-2-induced thermal hyperalgesia in mice. Grant et al (2007) found that PAR-2 also colocalized with TRPV4, SP and CGRP in dorsal root ganglia, that PAR-2 agonists enhanced TRPV4-induced calcium transients and whole-cell currents and that inhibition of phospholipase Cβ, PKA, PKC and PKD prevented the PAR-2-induced sensitization of TRPV4-induced responses. They also found that activation of TRPV4 stimulated the release of SP and CGRP from dorsal horn neurones and this release was potentiated by PAR-2 activation, similar to their previously demonstrated PAR-2 enhancement of TRPV1 release of SP and CGRP (Amadesi et al 2004).…”
mentioning
confidence: 96%
“…How does PAR-2 signalling lead to thermal and mechanical hyperalgesia? A global network of research groups, headed by Nigel Bunnett, have presented a set of tour de force studies showing that PAR-2 activates multiple second messenger pathways to sensitize TRPV1 and TRPV4 receptors on nociceptive neurones and this, in turn, releases nociceptive peptides (SP and CGRP) onto centrally projecting nociceptors that can account for TRPV1-dependent thermal and TRPV4-dependent mechanical hyperalgesia (Amadesi et al 2006;Grant et al 2007). TRPV1 and TRPV4 receptors are calcium-permeable cationic ion channels activated by multiple sensory stimuli; of relevance here is that TRPV1 can be gated by noxious heat (> 42 • C) and capsaicin, and TRPV4 by warm temperature (> 27 • C), hypotonicity and shear stress (Nilius et al 2004).…”
mentioning
confidence: 99%
“…TRPV4 is expressed in different neuronal and non-neuronal cells, including urinary bladder, kidney, vascular endothelium, keratinocytes, cochlear hair cells, and Merkel cells [85][86][87]. Likewise the TRPV1 channel, TRPV4 activation on TG or DRG neurons [84,88] causes SP and CGRP release, thus evoking neurogenic inflammation in peripheral tissues [89]. TRPV4 was firstly identified as an osmo-transducer activated by decrease in osmolarity, suggesting a role in the regulation of cell swelling [84,90].…”
Section: Trpv4mentioning
confidence: 99%
“…Indeed, PGE 2 and serotonin can act synergistically through cAMP/protein kinase (PK) A (PKA) and PKC to engage TRPV4 in hyperalgesia to mechanical and osmotic stimuli [99]. In addition, protease-activated receptor 2 (PAR 2 ) agonists may sensitize TRPV4 through the activation of multiple second messenger pathways, such as PKA, PKC, PKD, and PLC [89]. Proteases generated during inflammation activate PAR 2, thus leading to TRPV4-mediated release of SP and CGRP in the spinal cord and TRPV4-induced mechanical hyperalgesia [100].…”
Section: Trpv4mentioning
confidence: 99%